Manajemen Stres untuk Menurunkan Kecemasan Menghadapi Ujian Nasional Siswa Sekolah Menengah Pertama - Friandry W Thoomaszen; Murtini Murtini (Universitas Ahmad Dahlan, 2014)
ABSTRACTStudents experienced anxiety and fear when facing the National Exam because they think it is pressed. In addition, it is caused by the lack of the resources to deal with the final exam. The research aim was tested the stress management training based on the procedure of Stress inoculation training (SIT) in the junior high school students who experienced anxiety facing the final exam.The research hypothesis was that stress management training could reduce the anxiety facing the final exam at the Junior High School students. The scale questionaire used to measure the anxiety. The research method was quasi-experiment. The results of analysis with the mixed ANAVA techniqueshowed that the stress management training by the SIT procedure could significantly decreased anxiety when facing the final exam in junior high school students in Kupang (F = 17.192, p <0.01), with the effective contribution about 86.7%. Junior high school students who had received the stress management training decreased level of anxiety to face the final exam more significantly than those who did not received the stress management training.Key word: adolescence, anxiety, stress management.